2017
DOI: 10.1111/tme.12431
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HNA alloimmunisation risk in Northeastern Thais, Burmese and Karen

Abstract: This is the first study that reported the allele frequencies of HNA-1, -3, -4, and -5 in a large sample of healthy unrelated individuals from ethnic Thais, Burmese and Karen. Our results indicated the high possible risk of HNA-1, -3 and -5 alloimmunisation in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…The genotype frequencies of heterozygous HNA-1a/b between the Chinese and populations of German and British were similar, whereas the gene frequencies of HNA-1a/b between the Chinese and populations of Danish and Zambians were quite different. Similar findings have also been reported by Simtong et al (2017). As antibodies against HNA-1b have been associated with ANN (Tomicic et al, 2009), the lower HNA-1b gene frequency, consistent with reports in other Asian populations, may suggest that there may be a lower incidence rate of ANN in Asians compared to some Western countries.…”
Section: Comparing Hna Allele and Genotype Frequencies In Hong Kong Csupporting
confidence: 88%
See 1 more Smart Citation
“…The genotype frequencies of heterozygous HNA-1a/b between the Chinese and populations of German and British were similar, whereas the gene frequencies of HNA-1a/b between the Chinese and populations of Danish and Zambians were quite different. Similar findings have also been reported by Simtong et al (2017). As antibodies against HNA-1b have been associated with ANN (Tomicic et al, 2009), the lower HNA-1b gene frequency, consistent with reports in other Asian populations, may suggest that there may be a lower incidence rate of ANN in Asians compared to some Western countries.…”
Section: Comparing Hna Allele and Genotype Frequencies In Hong Kong Csupporting
confidence: 88%
“…Similar findings have also been reported by Simtong et al . (). As antibodies against HNA‐1b have been associated with ANN (Tomicic et al, ), the lower HNA‐1b gene frequency, consistent with reports in other Asian populations, may suggest that there may be a lower incidence rate of ANN in Asians compared to some Western countries.…”
Section: Discussionsupporting
confidence: 60%
“…Although there has been studied on RBC phenotype frequencies in ethnic Thai populations (Fongsarun et al, ), there are no data from north‐east Thailand. Our previous studies on other aspects of molecular genetics, such as human leucocyte antigens (HLA), human neutrophil antigens (HNA) and killer immunoglobulin‐like receptors (KIRs), revealed significant differences in frequency of alleles/molecules in different regions of Thailand (Chaisri et al, ; Romphruk et al, ; Simtong et al, ). Here, we report for the first time the antigen and phenotype frequencies of blood group systems (Rh, M, Mi a and Kidd) by gel technology among ethnic Thai blood donors in the north‐east of Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…Until today, this fact impedes routine antibody screening for many laboratories. In addition, neutrophil donors expressing rare HNA antigen (such as HNA‐1c) are difficult to obtain, especially in certain regions with low allelic frequency (Asian compared to Caucasian population) . However, anti‐HNA‐1c alloantibodies play an important role on the mechanism of severe NAIN .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neutrophil donors expressing rare HNA antigen (such as HNA-1c) are difficult to obtain, especially in certain regions with low allelic frequency (Asian compared to Caucasian population). 22 However, anti-HNA-1c alloantibodies play an important role on the mechanism of severe NAIN. 23 Recent data from our laboratory indicated that anti-HNA-1c alloantibodies aroused more frequently than expected, but may often be covered by the presence of anti-HNA-1b alloantibodies in serum samples.…”
Section: Discussionmentioning
confidence: 99%